2021
DOI: 10.3390/ijms22052540
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Estrogenic Activity and Site-Specific Accumulation of Bisphenol-A in Epididymal Fat Pad: Interfering Effects on the Endocannabinoid System and Temporal Progression of Germ Cells

Abstract: The objective of this work has been to characterize the estrogenic activity of bisphenol-A (BPA) and the adverse effects on the endocannabinoid system (ECS) in modulating germ cell progression. Male offspring exposed to BPA during the foetal-perinatal period at doses below the no-observed-adverse-effect-level were used to investigate the exposure effects in adulthood. Results showed that BPA accumulates specifically in epididymal fat rather than in abdominal fat and targets testicular expression of 3β-hydroxys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The Wnt/β-catenin signalling pathway is a key pathway that regulates spermatogenesis [ 23 ]. Chioccarelli et al investigated the effects of bisphenol A (BPA) on germ cells and showed that BPA increases the content of germ cells (spermatogonia), reduces the population of spermatocytes and sperm cells, accelerates the process of spermatocyte and sperm cells, and promotes the epithelial exfoliation of round and concentrated sperm cells; these phenomena are accompanied by the downregulation of β-catenin [ 24 ]. In the present study, the proliferation of rat spermatogonia is facilitated by the silencing of CAM2D .…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β-catenin signalling pathway is a key pathway that regulates spermatogenesis [ 23 ]. Chioccarelli et al investigated the effects of bisphenol A (BPA) on germ cells and showed that BPA increases the content of germ cells (spermatogonia), reduces the population of spermatocytes and sperm cells, accelerates the process of spermatocyte and sperm cells, and promotes the epithelial exfoliation of round and concentrated sperm cells; these phenomena are accompanied by the downregulation of β-catenin [ 24 ]. In the present study, the proliferation of rat spermatogonia is facilitated by the silencing of CAM2D .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several epidemiological and experimental studies have highlighted specific male reproductive defects depending on the type of contaminant and on the exposure window ( Barakat et al , 2019 ; Campos et al , 2019 ; Selvaraju et al , 2021 ). In particular, EC exposure impairs spermatogenesis and gamete health by inducing multiple anomalies, such as: deregulation of spermatogenic cycle timing; production of reactive oxygen species (ROS); Sertoli and germ cell apoptosis; germ cell abnormal chromosomal segregation and DNA fragmentation; steroidogenesis defects; disruption of blood-testis-barrier integrity and permeability; and alteration of sperm morphology and motility ( Jeng, 2014 ; Easley et al , 2015 ; Governini et al , 2015 ; Qiu et al , 2016 ; Aydin and Erkan, 2017 ; Jia et al , 2017 ; Rodríguez et al , 2017 ; Zhang et al , 2018 ; Santoro et al , 2019 ; Maske et al , 2020 ; Chioccarelli et al , 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…By looking at the content of reproductive research, it was possible to determine its trends. Among the selected papers, about half were related to male reproduction, e.g., testis and sperm, [1][2][3][4][5][6][7][8][9][10][11][12], and the other half were associated with female reproduction, e.g., oocytes, as well as embryos and their implantation, including three reviews [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%